Indian South Africans: (be)-longing and the post-apartheid search for roots and the imagined family. Issue 1 (2nd January 2019) - Desai, Ashwin
ABSTRACT: The Indian Relief Act of 1914 severely curtailed the right of Indians to settle in South Africa. As the twentieth century unfolded and the South African government passed a succession of discriminatory laws against Indians, Indian nationalists sought the isolation of the white minority regime. This increased the 'distance' between Indian South Africans and India. The ending of apartheid and the normalization of relations between India and South Africa opened the doors to travel and reconnections with the 'motherland'. In this context of changing relations, this article explores the renewed links between Indian South Africans and the 'motherland', some because of the increasing popularity of 'roots tourism' in which they seek to visit their forbears' village of origin and meet with relatives after more than a century of separation, others because they are interested in applying for the Overseas Citizen of India card, and yet others because of their renewed pride in 'shining India'. The article concludes with a reflection on the utility of the idea of diaspora in the light of the experience of Indian South Africans' search for roots.